Modification of the flora composition in edges of fragmented Austrocedrus chilensis forests in Patagonia - Carabelli, F.A.=700 1 Orellana, I.A.; Jaramillo, M.M.; Gomez, F.F.
(En, Es)
ilus., 38 ref.
Keywords: LIBOCEDRUS; COMPOSICION BOTANICA; REGENERACION; ESPAÑA; EFECTO DE BORDE; INFLUENCIA ANTROPICA; GRADIENTE DE VEGETACION; PATAGONIA